Creative Marketing Strategies to Increase Interest in SDN 8 Sumberagung - Bayani, Mufasirul (SAINTIS Publishing, 2024)
This research aims to explore the creative marketing strategies implemented at SDN 8 Sumberagung to increase public interest in schools. Using a descriptive qualitative approach with a case study method, this study collects data through in-depth interviews, observations, and documentation. Interviews were conducted with school principals, teachers, administrative staff, as well as parent representatives and community leaders, while observations were carried out to record promotional activities carried out by the school. The data is analyzed using thematic analysis techniques, identifying key themes in the applied marketing strategy. The results of the study show that the use of social media, personal approach, and differentiation of superior programs have proven to be effective in attracting public interest. Social media such as WhatsApp and Facebook are successfully used to disseminate information with creative content, while a personal approach through home visits builds an emotional connection with parents. In addition, the environment-based learning program and practical skills provide a competitive advantage that sets SDN 8 Sumberagung apart from other schools. Overall, the study shows that creative marketing strategies tailored to local conditions can improve the school's image and the number of new student enrollees in rural environments.